Integrating biophilic design in multi-generational housing: a conceptual framework for enhancing well-being and quality of life - Che Wil @ Ismail, Che Muhamad Hanif; Ismail, Hafiszah (UiTM Press, 2025)
This paper explores the integration of biophilic design principles into multigenerational housing environments to enhance the well-being and quality of life (QoL) of residents in Malaysia. Through biophilic design, the study aims to develop a conceptual framework that identifies key factors contributing to improved mental health, reduced stress, and overall QoL in multi-generational households. Adopted a scoping review methodology, using secondary data from the existing literature published between 2019 and 2024 to build the framework. The analysis consisted of a concept matrix to collate the data that has been collected and determine the key drivers of housing environment preference along with the sub-factors. Overall, the findings suggest that biophilic design elements like natural light, ventilation, green spaces and views of nature greatly contribute to residents' wellbeing across generations. Additionally, the research also discovered that Generation Alpha, Millennials, Generation X and Baby Boomers have such different needs which means spaces must be built for them all. The conceptual framework therefore provides a pragmatic guide that targets improved QoL by integrating biophilic principles in the design of multigenerational housing to alleviate stress, which is detrimental to mental health, among residents. This framework should help architects, urban planners and policymakers working towards healthier and more sustainable living environments.